Does institutional ownership increase market quality? Empirical evidence from the financial crisis - CHEN, ZIJIE (2020)
This dissertation aims to examine the relationship between institutional ownership and stock market quality. By using stock data from US S&P 500 index constituent, this dissertation empirically studied how the volatility, returns, and liquidity of the stocks are impacted by institutional investors. This dissertation also considered the impact of the 2008 financial crisis and the short sale restrictions enforced during the crisis. According to the OLS regression results, this paper discovered there is a positive association between institutional ownership and stock return and liquidity. There is a negative correlation between institutional ownership and stock return volatility. Besides, this dissertation further study how different is the impact of institutional ownership on financial stocks and non-financial stocks. The positive impact of institutional ownership on the return of financial stocks is weaker than non-financial stocks, and the impact of institutional ownership on volatility and bid-ask spread of financial stocks is positive. In addition, the impact of institutional ownership on volatility and liquidity of financial stocks is weakened by the short sale restrictions. The financial crisis also weakens the impact of institutional ownership on volatility and bids-ask spread of non-financial stocks.